'Opening the door': A qualitative interpretive study of women's experiences of being asked about intimate partner violence and receiving an intervention during perinatal home visits in rural and urban settings in the USA. (September 2016) - Bacchus, Loraine J; Bullock, Linda; Sharps, Phyllis; Burnett, Camille; Schminkey, Donna; Buller, Ana Maria; Campbell, Jacquelyn
This study explored women's experiences of being screened for intimate partner violence and receiving an intervention during perinatal home visits in urban and rural settings in the USA. Twenty-six women were recruited from the DOVE (Domestic Violence Enhanced Home Visit) intervention trial to participate in a nested qualitative interpretive study. Women valued the opportunity to discuss their intimate partner violence experiences and access support. Disclosure was a staged process and home visitor communication style and the development of a trusting relationship were influencing factors. Safety planning was an important feature of the DOVE intervention, whether the abuse was past or ongoing. Women highlighted the need for post-abuse support services. Perinatal home visitors require training in intimate partner violence that supports the development of good communication skills and provides opportunities for experiential learning and feedback with regards to asking about and responding to intimate partner violence. Reinforcement training activities are necessary in order to enhance home visitor's confidence and comfort, and sustain practice. Rigorous protocols are needed to ensure the safety of home visitors and women.